Human cytosolic asparaginyl-tRNA synthetase: cDNA sequence, functional expression in Escherichia coli and characterization as human autoantigen. - Beaulande, M (1998)
The cDNA for human cytosolic asparaginyl-tRNA synthetase (hsAsnRSc) has been cloned and sequenced. The 1874 bp cDNA contains an open reading frame encoding 548 amino acids with a predicted M r of 62 938. The protein sequence has 58 and 53% identity with the homologous enzymes from Brugia malayi and Saccharomyces cerevisiae respectively. The human enzyme was expressed in Escherichia coli as a fusion protein with an N-terminal 4 kDa calmodulin-binding peptide. A bacterial extract containing the fusion protein catalyzed the aminoacylation reaction of S.cerevisiae tRNA with [14C]asparagine at a 20-fold efficiency level above the control value confirming that this cDNA encodes a human AsnRS. The affinity chromatography purified fusion protein efficiently aminoacylated unfractionated calf liver and yeast tRNA but not E.coli tRNA, suggesting that the recombinant protein is the cytosolic AsnRS. Several human anti-synthetase sera were tested for their ability to neutralize hsAsnRSc activity. A human autoimmune serum (anti-KS) neutralized hsAsnRSc activity and this reaction was confirmed by western blot analysis. The human asparaginyl-tRNA synthetase appears to be like the alanyl- and histidyl-tRNA synthetases another example of a human Class II aminoacyl-tRNA synthetase involved in autoimmune reactions.